2021
DOI: 10.1371/journal.pone.0245239
|View full text |Cite
|
Sign up to set email alerts
|

Hmx1 regulates urfh1 expression in the craniofacial region in zebrafish

Abstract: H6 family homeobox 1 (HMX1) regulates multiple aspects of craniofacial development as it is widely expressed in the eye, peripheral ganglia and branchial arches. Mutations in HMX1 are linked to an ocular defect termed Oculo-auricular syndrome of Schorderet-Munier-Franceschetti (MIM #612109). We identified UHRF1 as a target of HMX1 during development. UHRF1 and its partner proteins actively regulate chromatin modifications and cellular proliferation. Luciferase assays and in situ hybridization analyses showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…Previously, we identified uhrf1 as an hmx1 target gene, and it has been implicated in the regulation of several developmental and homeostatic processes related to zebrafish development. In situ hybridization in hmx1 transgenic and mutant zebrafish showed that uhrf1 expression is modulated in the hindbrain, eye region, and branchial arches [ 33 ]. Potentially, uhrf1 could change the methylation pattern of bmp2b and bmp4 and, therefore, induce gene transcription.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we identified uhrf1 as an hmx1 target gene, and it has been implicated in the regulation of several developmental and homeostatic processes related to zebrafish development. In situ hybridization in hmx1 transgenic and mutant zebrafish showed that uhrf1 expression is modulated in the hindbrain, eye region, and branchial arches [ 33 ]. Potentially, uhrf1 could change the methylation pattern of bmp2b and bmp4 and, therefore, induce gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…All embryos at desired stages were kept in Danieau’s solution with 0.003% 1-phenyl-2-thiourea (Sigma, Buchs, Switzerland) to suppress pigmentation. The zebrafish mutant lines hmx1 mut10 and hmx1 mut150 were previously generated and described [ 33 ]. Briefly, hmx1 mut10 zebrafish have a frameshift mutation that generates a termination codon in the SD1 domain, while mutant hmx1 mut150 has an indel mutation that replaces the HD domain; dimerization of SD1 and HD is necessary for the proper function of hmx1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of UHRF1 is also regulated by several proteins, including E2F1 (E2F transcription factor 1), E2F8 (E2F transcription factor 8), FOXM1 (forkhead box protein M1), SP1 (specificity protein 1), SHMT2 (serine hydroxymethyltransferase-2), Setd1a (SET domain containing 1A, histone lysine methyltransferase), and Hmx1 (H6 family homeobox 1). Moreover, the activity of CD47 (cluster of differentiation 47) integrins increases UHRF1 expression in different cancers and represses the activity of many tumor-suppressor proteins [ 58 , 59 , 60 , 61 , 62 , 63 ]. Finally, the downregulation of various regulatory mi-RNAs leads to a high-level expression of UHRF1 proteins in cancers [ 64 , 65 ].…”
Section: Uhrf1 Expression and Its Regulationmentioning
confidence: 99%
“…It is characterized by complex ophthalmological and external ear anomalies as well as aberrant orofacial development with underdeveloped and asymmetric jaws [37]. OAS is caused by homozygous pathogenic variants in HMX1 (H6 Family Homeobox 1), encoding a homeobox transcription factor with high affinity toward a consensus HMX-binding site harboring a 5 -CAAGTG-3 element required for sensory organ development [65][66][67][68]. HMX1 is highly conserved across orthologs and contains three essential domains: a homeobox domain (HD) and conserved domains SD1 and SD2 [37,65,66].…”
Section: Schorderet-munier-franceschetti Syndromementioning
confidence: 99%